The impact of surgical closure of atrial septal defect on the pulmonary hypertension: a prospective observational study - Maruf, M. Abul Bashar; Hossain, Aslam; Nishat, Farhat Tabassum; Azad Liza, Kohinur; Azim, Anowarul; Shanta, Tania Nusrat; Ahaduzzaman, M.; Tiwari, Manoj; Jha, Vivek Kumar; Saquib, Mirza M. Nazmus (International Journal of Research in Medical Sciences, 2024)
Introduction: The most prevalent congenital disease is atrial septal defect. Atrial septal defects that have a left to right shunt result in persistent volume overload in the pulmonary vasculature. So histological changes occur in pulmonary vasculature leads to pulmonary hypertension. Without surgery, both life expectancy and functional ability are reduced. The aim of this study was to observe the impact of surgical closure of atrial septal defect on pulmonary hypertension. Methods: This observational study was done in the department of cardiac surgery, Bangabandhu Sheikh Mujib Medical University from June 2020 to June 2022. Sample size was 24 Patients were evaluated preoperatively, postoperative day of operation through a clinically, ECG, color doppler echocardiography. The statistical analysis was performed by using SPSS version 26.0 for windows software. Results: In my study, the mean age of the patients was 33.33±11.3 years, male female ratio was 1:2. The mean pulmonary artery systolic pressure got decreased from 57.54±7.9 mmHg to 53.29±8.30 mmHg on postoperative day. 75% patients improved into New York heart association class 2 on post operative day. Significant improvement was seen in functional capacity of the patients. 29.2% patients had atrial fibrilation preoperatively, after surgery on post-operative day it became 25%. Conclusions: This study concludes that surgical closure of atrial septal defect leads to a significant reduction in pulmonary hypertension.